Alaskan Permafrost Groundwater Storage Changes Derived from GRACE and Ground Measurements - Reginald R. Muskett; Vladimir E. Romanovsky (Remote Sensing, 2011)
The Arctic is in transition from climate-driven thawing of permafrost. We investigate satellite-derived water equivalent mass changes, snow water equivalent with in situ measurements of runoff and ground-survey derived geoid models from 1999 through 2009. The Alaskan Arctic coastal plain groundwater storage (including wetland bog, thaw pond and lake) is increasing by 1.15 ± 0.65 km3/a (area-average 1.10 ± 0.62 cm/a), and Yukon River watershed groundwater storage is decreasing by 7.44 ± 3.76 km3/a (area‑average 0.79 ± 0.40 cm/a). Geoid changes show increases within the Arctic coastal region and decreases within the Yukon River watershed. We hypothesize these changes are linked to the development of new predominately closed- and possibly open-talik in the continuous permafrost zone under large thaw lakes with increases of lakes and new predominately open-talik and reduction of permafrost extent in the discontinuous and sporadic zones with decreases of thaw lakes.